The Urgency Of Shifting The Regulation Of Enforcement Of Fisheries Criminal Laws From Criminal Sanctions To Administrative Sanctions - Fathurrahim Fathurrahim; Muhaimin Limatahu; Ahmad Mufti (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the urgency of shifting the paradigm of fisheries crime law enforcement from the dominance of criminal sanctions to the strengthening of administrative sanctions. Previous studies have focused more on the effectiveness of criminal sanctions or technical administrative implementation, but have not criticized the dominance of the penal approach, which has led to problems of imbalance in law enforcement, where criminal instruments are used extensively without considering the nature of the offense and the capacity of the perpetrator. This condition has implications for the emergence of legal uncertainty, inefficient judicial burdens, and a lack of corrective effects on the main actors in fisheries crime. This research gap is the main basis for conducting this study. The method used is normative legal research with a legislative, conceptual, and comparative approach, enriched with limited empirical analysis through a review of law enforcement practices and court decisions. The results of the study show that criminal sanctions have so far been ineffective in targeting the main actors (corporations), while administrative sanctions—such as license revocation, administrative fines, and business freezing are more strategic because they are responsive, adaptive, and in line with global practices. However, its effectiveness is still hampered by institutional capacity, accountability in implementation, and unequal treatment between large operators and small-scale fishermen. The research conclusion emphasizes the novelty of offering a reorientation of fisheries law that places administrative sanctions as the primary instrument (primum remedium), while criminal sanctions are positioned selectively as the last resort (ultimum remedium). Thus, this study offers a new conceptual framework that is more progressive, fair, and sustainable in the enforcement of Indonesian fisheries law.